Condylar process and temporomandibular disorders in orthognathic patients: crosssectional study - Maria Fernanda Pivetta Petinati; Paola Fernanda Cotait de Lucas Corso; Juliana Feltrin de Souza; Nelson Luis Barbosa Rebellato; Rafaela Scariot; Delson João da Costa (Revista Sul-Brasileira de Odontologia, 2022)
The temporomandibular joint seems to respond to functional demands as it is continually subjected to remodeling, which affects volume and shape. Altered functioning can lead to TMJ overload, resulting in temporomandibular disorders. Objective: This study evaluates condylar anatomical changes and temporomandibular dysfunctions in orthognathic patients. Material and methods: This cross-sectional study was evaluated 174 Patients were between 18 and 57 years old representing facial patterns I (n = 51), II (n = 59), and III (n = 64). Morphology, morphometry and volumetry of 348 condylar processes were analyzed using cone beam computed tomography. Diagnosis of TMD was evaluated using Research Diagnostic Criteria for TMD (RDC/TMD). P values <0.05 were considered significant. Results: Patients with facial pattern II had more morphological changes than I (p <0.05). For morphometric analysis, the width of the condylar processes among patients with pattern II was shorter than I and III (p <0.001). Height of the condylar processes in patients with pattern III was greater than I and II (p <0.001). Volume of the left condylar process in patients with pattern II was lower than I p = 0.02). Muscle disorders and other joint conditions were more common in women than men (p <0.05). Patients with pattern II had more muscular disorders and other joint conditions than I (p <0.05). Patients with pattern III showed more muscle disorders and disc displacement than I (p <0.05). Conclusion: Orthognathic patients have condylar anatomical changes that may facilitating temporomandibular disorders when compared to non-orthognathic patients. Condylar process morphology and morphometry can make it possible to define an anatomical pattern to contribute to decision[1]making regarding the treatment or not of a given temporomandibular disorders.